Ensaio sobre a relação entre Estado, políticas públicas de turismo e desenvolvimento regional no Brasil - Rita de Cássia Ariza da Cruz (Confins)
Despite the profound changes that directly affect the role of the State in the economic, social and political development of nations, it continues to determine "the structure in which public and private activity occurs" (Hall 2001), that is, the centrality of the State in the social reproduction remains unquestionable, including its protagonism in the promotion of the economic activity of tourism. Based on this assumption, the objective of this article is to analyze federal public tourism policies implemented in Brazil between 1990 and 2010, considering their central objectives, announced in official documents. Among the results we are confronted, firstly, with a fragile convergence between the guiding objectives of the policies analyzed. In addition, these objectives favor economic aspects and the implementation of infrastructures, evidencing the promotion of processes of capital devaluation, promoted by the State, which, in terms of regional development, are carried out in a dialectical relation with the unequal Brazilian geographical development.